DESAIN PRIMER BERDASARKAN GEN MT-12S rRNA UNTUK MENDETEKSI CEMARAN DAGING BABI PADA PRODUK OLAHAN ASAL DAGING SAPI DENGAN METODE MULTIPLEKS-PCR - Sitompul, Yeremia Yobelanno; Artanto, Sidna (Jurnal Sain Veteriner, 2025)
The case of adulteration of pork in beef products, which causes fretfulness especially for muslims, is still found in Indonesia. Multiplex Polymerase Chain Reaction (Multiplex PCR) can help detecting the adulteration of pork in beef products. This method needs multiple specific primers to amplify several targeted DNA mixture in single step reaction. This study aimed to design specific primers that can be utilized to detect the adulteration of pork in beef products using Multiplex PCR method.Firstly, primers were designed in silico using bioinformatic tools which were MegAlign, Seqbuilder, and AmplifX. This design was based on mt-12s rRNA gene. The length of amplified fragment using the designed primers for cow was 91 bp, while the pig was 230 bp. Secondly, the designed primers were tested to amplify DNA of cow and pig from raw beef, pork, mixture of beef and pork, and twelve samples of their products (meatballs) to assess their ability to amplify targeted DNA spesifically.The result showed that the designed primers could amplify the targeted DNA specifically from raw beef, pork, mixture of both meat, and their products. Therefore, the designed primers evidently can be used to detect adulteration of pork in beef by Multiplex PCR method.